A influência da cultura organizacional na gestão da criatividade: um estudo exploratório na Escola de Samba Vai-Vai - Santos, Márcio Cardoso (2012)
The expression of creativity in organizations has been seen as an important factor for institutions who want innovation. The constant changes in the environment which organizations operate has required of individuals, within institutions, creative actions in order to promote organizational innovations. It becomes necessary for organizations to build an environment that fosters the creative expression of people as a means of achieving the desired results. Organizational culture consists of the principles, values, beliefs, constitutes an important element in the process of building a favorable environment for the expression of creativity within organizations.This work studies the influence of organizational culture in the management of creativity, as a case study with the samba school Vai Vai. Aims to reflect and analyze the issue of organizational culture and its influence on the management of creativity in the samba school Vai Vai. The samba school is an entity that, by its very nature, creativity flows, having been created as a means for the population could play the carnival. Regulations established by the Carnival parade the samba schools promote big shows on the avenue, aiming to surprise and thrill the viewing public and the jury, with a view to winning the championship. The theoretical studies show the importance of building a culture of creativity as one of the elements inserted in the process of managing creativity. Moreover, they express the difference between creativity and innovation, essential to a proper understanding of the subject matter. The field study was conducted through interviews with board members of the Vai Vai, as well as by direct observation of events and testing by the club. It was identified that the Vai Vai presents an organizational culture that encourages creative expression in the institution, it was concluded that the guild has the characteristics of creative organizations